Ag-doped TiO2 hollow microspheres with visible light response by template-free route for removal of tetracycline hydrochloride from aqueous solution. (6th June 2018) - Zhang, Jian; Li, Xuanhua; Peng, Meiling; Tang, Yuanyuan; Ke, Anqi; Gan, Wei; Fu, Xucheng; Hao, Hequn
Abstract: In this study, Ag-doped TiO2 hollow microspheres were synthesized by a template-free route, and their photocatalytic performance and catalytic mechanism were investigated. The hollow microspheres were characterized by x-ray diffraction, scanning electron microscopy, transmission electron microscopy, x-ray photoelectron spectroscopy and UV–vis spectroscopy. Ag-doped hollow TiO2 microspheres exhibited excellent photocatalytic performance for tetracycline hydrochloride (TC) in water. TC degradation follows pseudo first-order kinetics, and hydroxyl radical (OH·) and holes (h + ) were active substances in the photocatalytic reaction.